Effects of Hall current and rotation - Raptis A.; Ram P.C. (My University, 2025)
Effects of Hall current and rotation on the flow of electrically conducting rarefied gas due to combined buoyant effects of thermal and mass diffusion, past an infinite porous plate in the presence of transverse magnetic have been investigated. The equations governing the flow problem have been solved and the profiles are shown on graphs. Effects of m (Hall parameter) and E (Ekman number) on velocity are discussed. © 1984 D. Reidel Publishing Company.